2022
DOI: 10.1108/scm-05-2021-0256
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management in offshoring innovation by SMEs: role of internal knowledge creation capability, absorptive capacity and formal knowledge-sharing routines

Abstract: Purpose In spite of the increased attention on knowledge management processes as important variables for firms to generate performance benefits within supply chain literature, little is known about how these variables could impact offshoring innovation (OI) relationships held by small and medium-sized enterprises (SMEs). Considering their growing importance, this study aims to investigate the interplay between the internal knowledge creation capability, absorptive capacity and formal knowledge routines in atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 127 publications
1
24
0
1
Order By: Relevance
“…Based on the mediation-moderation analysis, Khraishi et al (2022) demonstrated that absorptive capacity and internal knowledge creation capacity influence offshoring innovation performance, while absorptive capacity mediates the relationship between internal knowledge creation and offshoring innovation performance. Further, their findings indicate that formal knowledge sharing routines moderate the relationship between absorptive capacity and offshoring innovation performance.…”
Section: Table 11 Articles On Knowledge Measurement and Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Based on the mediation-moderation analysis, Khraishi et al (2022) demonstrated that absorptive capacity and internal knowledge creation capacity influence offshoring innovation performance, while absorptive capacity mediates the relationship between internal knowledge creation and offshoring innovation performance. Further, their findings indicate that formal knowledge sharing routines moderate the relationship between absorptive capacity and offshoring innovation performance.…”
Section: Table 11 Articles On Knowledge Measurement and Performancementioning
confidence: 99%
“…, Alegre et al (2013), Audretsch and Belitski (2021), Azyabi (2018), Bloem and Salimi (2022), Byukusenge and Munene (2017) Hassan and Raziq (2019), Kmieciak and Michna (2018), Khraishi et al (2022), Lee and Wong (2015a, b), Liu and Abdalla (2013), Obeso et al (2020), Permatasari et al (2022), Santoro et al (2019), Schoenherr et al (2014), Scuotto et al (2020, Ul Zia (2020), Wang and Yang (2016), Wibowo and Grandhi (2017), Yusr et al (2021)…”
mentioning
confidence: 99%
“…Innovativeness is considered a process that exploits creative ideas for commercial gain and the benefit of the firm (Chatterjee, 2021;Khraishi et al, 2022). Therefore, creativity and innovation are found to work in tandem (Escrib a-Esteve and Montoro-S anchez, 2012).…”
Section: Knowledge Management Practices In Firmsmentioning
confidence: 99%
“…In recent decades, the literature has analyzed the AC mediation effect on firm performance and found a significant positive relationship between the variables tested. For instance, conceptual ambiguity of AC (Song et al, 2018), innovation and mass customization (Liu et al, 2018), internal cost management, information systems integration, AC and interorganizational cost management (Fayard et al, 2012), knowledge management in offshoring innovation by small and medium-sized enterprises (SMEs) (Khraishi et al, 2022), among others.…”
Section: 4mentioning
confidence: 99%
“…, 2018), internal cost management, information systems integration, AC and interorganizational cost management (Fayard et al. , 2012), knowledge management in offshoring innovation by small and medium-sized enterprises (SMEs) (Khraishi et al. , 2022), among others.…”
Section: Literature Reviewmentioning
confidence: 99%